a comic culture called carnival (Mayéutica Revista Científica de Humanidades y Artes, 2025)
Carnival, says Russian philosopher and philologist Mikhail Bakhtin (1895-1975), is a semiotic system that has been built up over the centuries. The language of carnival permeated the literature and utopian musings of the Renaissance. The world in which François Rabelais (1483-1553), the great figure of 16th-century French and world literature, was a carnivalesque world of popular inspiration, of the public square, which allowed him to write Gargantua and Pantagruel, the embodiment of the essence of carnival, and which can be clearly seen in Peter Brueghel the Elder's brilliant painting The Battle Between Carnival and Lent, painted in 1559.
Keywords: carnival; culture; literature